2018
DOI: 10.1080/19393210.2018.1505781
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in seafood purchased from a fishery market in Hungary

Abstract: Heavy-metal content (arsenic, cadmium, lead and mercury) was investigated and evaluated in shellfish, oysters and squids. The samples were collected weekly for 20 weeks from a fishery product market in Hungary. The concentration of heavy metals was measured by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES) analysis after sample preparation. The results were analysed statistically by one-way ANOVA method. The average concentration of arsenic (3.01 ± 1.46 mg kg) in shellfish was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Compared with other studies, Guéguen et al, (2011) found the similar mean level of cadmium (0.15 mg/kg) in mussels from France as in the present investigation. Lehel et al, (2018) determined slightly higher mean values in shell sh marketed in Hungary, up to 0.26 mg/kg. Joksimovic and Stankovic, (2011) reported a higher mean concentration of Cd (0.84 mg/kg) in mussel's tissue from Montenegro.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Compared with other studies, Guéguen et al, (2011) found the similar mean level of cadmium (0.15 mg/kg) in mussels from France as in the present investigation. Lehel et al, (2018) determined slightly higher mean values in shell sh marketed in Hungary, up to 0.26 mg/kg. Joksimovic and Stankovic, (2011) reported a higher mean concentration of Cd (0.84 mg/kg) in mussel's tissue from Montenegro.…”
Section: Resultsmentioning
confidence: 88%
“…According to the Australia standard and EU ( 2001), the maximum level permitted for arsenic in sh is 1.0 mgkg -1 . Lehel et al (2018) found a mean total arsenic concentration of 3.01 mg/kg in shell sh. Joksimovic and Stankovic (2011) (Lehel et al 2018;WHO, 2021).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…(Harada, 1995;Roditi & Fisher, 1999;Takaoka et al, 2008). As a result, Hg safety in fish and shellfish has gradually become the focus of people's attention (Lehel et al, 2018). However, the relationship between the concentration of dissolved Hg(II) in water and the content of Hg and MeHg in aquatic products has not been elucidated, so it is urgent to find a model for simulation calculations of Hg.…”
Section: Introductionmentioning
confidence: 99%